Mortality Risk factors and SOX2 and mTOR expression in Patients with Esophageal Cancer - Yu, Gao; Yuexin, Yang; Yin, Lv; Yiyin, Zhang; Mei, Kang; Liyang, Zhu; Lei, Xu; Fan, Wang (Cellular and Molecular Biology, 2022)
Causes of mortality in EC patients are not confined to cancer-specific mortality but include various protein expressions of SOX2 and mTOR in Esophageal Cancer patients and their correlation with the clinical stage. Data about the risk factors and involvement of cancer-specific protein are still lacking. This study aimed to define the risk factors and association of SOX2 and mTOR expression in mortality in patients with EC. We conducted a retrospective cohort study to assess the risk factors for cancer-specific mortality and cardiovascular mortality in patients with esophageal cancer (EC). The expression rates of SOX2, as well as MTO, were checked in patients. The multivariate analysis revealed a high-risk EC mortality with age ≥ 65 years, black race, grade, stage, and sequence of treatment; radiation after surgery; radiation before and after surgery; Surgery both before and after radiation. While the cardiovascular mortality increased with age ≥ 65 years, adenocarcinoma type, grade, stage, and sequence of treatment. The expression rates of SOX2, as well as mTOR, were 75.5 percent and 86.8 percent in Esophageal Cancer, while were 10.7 percent and 7.5 percent in osteochondroma, respectively, which was statistically significant (P<0.05). Risk factors for cancer-specific mortality and cardiovascular mortality in EC patients include older age at diagnosis, male sex, non-married status, grade III of the tumor, the regional or distant spread of the tumor, no cancer-directed therapy. The expression levels of SOX2, mTOR, and the total survival time were related to the different stages. It shows an upward trend for the expression levels of mTOR and SOX2 in Esophageal Cancer tissues. The expression levels of SOX2 and mTOR are related to the clinical stage, metastasis, and prognosis.